Efficacy analysis of large-channel spinal endoscope unilateral laminotomy decompression for the treatment of multilevel cervical spinal stenosis with ligamentum flavum hypertrophy - Zheng, Yiping; Wang, Luyang; Zhao, Mingwang; Zhang, Yongchun; Yang, Donglin; Chen, Xiaoxin; Li, Xingchen; Xu, Yusheng (Frontiers in Surgery, 2025)
ObjectiveCervical spinal stenosis predominantly affects the elderly. After 40 years of age, aging induces progressive loss and rupture of elastic fibers in the ligamentum flavum, accompanied by abnormal proliferation and cross-linking of collagen fibers, as well as calcium salt deposition and even ossification. This study investigates the clinical efficacy and safety of large-channel endoscopic unilateral laminotomy decompression for the treatment of multilevel cervical spinal canal stenosis.MethodsA retrospective study was conducted on 36 Cervical spinal canal stenosis patients with radiologically confirmed who underwent surgical treatment between January 2020 and December 2023.Patients were divided into two groups according to the surgical method: endoscopic group (n = 16) and open group (n = 20).Perioperative Parameters (operative duration, incision length, intraoperative blood loss, hospitalization period were record and Clinical efficacy were systematically assessed using validated metrics: Visual Analog Scale, Japanese Orthopaedic Association score, Neck Disability Index. Radiographical parameters [C2–C7 Cobb angle, T1 slope, pavlov ratio (canal/vertebral body diameter)] are used to assess the decompression effect and stability of cervical spine.ResultsThe endoscopic group demonstrated significant advantages over the open group in operative time (1.6 ± 0.6 vs. 2.1 ± 0.2 h, P < 0.05), incision length (1.3 ± 0.1 vs. 9.5 ± 0.7 cm, P < 0.05), blood loss (12.4 ± 7.4 vs. 64.3 ± 19.5 mL, P < 0.05), and hospitalization duration (6.6 ± 1.1 vs. 8.6 ± 1.4 days, P < 0.05). Both groups showed significant postoperative improvements in VAS, JOA, and NDI scores compared to preoperative baselines (P < 0.05). At 1 month postoperatively, the endoscopic group exhibited superior VAS scores to the open group (2.69 ± 0.79 vs. 4.4 ± 0.88, P < 0.05), though no significant differences were observed at other time points. Radiographic outcomes at final follow-up revealed significantly better cervical Cobb angle (13.57 ± 2.29° vs. 16.34 ± 2.95°, P < 0.05) and T1 slope (22.62 ± 1.51° vs. 25.24 ± 2.41°, P < 0.05) in the endoscopic group. Conversely, the open group demonstrated greater postoperative spinal canal area and Pavlov ratio (P < 0.05). Complications included 2 cases of C5 nerve root palsy and 1 case of axial pain in the open group, while the endoscopic group had 1 case of transient muscle weakness. No reoperations were required.ConclusionThe large-channel endoscopic unilateral laminotomy decompression demonstrates satisfactory short-term efficacy in treating multilevel Cervical Spinal Stenosis with ligamentum flavum hypertrophy. This minimally invasive technique offers significant advantages including reduced surgical trauma, accelerated recovery, enhanced postoperative cervical stability and relatively higher patient satisfaction.